Persepsi Publik terhadap Pergantian Menteri Pendidikan: Studi Survei di Kalangan Mahasiswa dan Tenaga Pendidik - Fadhilah Sabrina; Tri Saputra; Faqih Fuadi Lahfi; Abdul Fadhil (Lembaga Pengembangan Kinerja Dosen, 2025)
The change of Minister of Education is often followed by new policies that cause various reactions among the public, including students and educators. This study aims to understand public perceptions of the change of Minister of Education and its implications for curriculum policy. This research uses a descriptive qualitative approach with a questionnaire-based interview data collection method to educators and students. The results showed that most respondents had positive expectations of the new minister, especially regarding improving the quality of education and reducing the administrative burden on teachers. However, there were concerns about repeated curriculum changes. Respondents emphasized the importance of inclusive communication, strengthening the role of teachers and improving education infrastructure. Active stakeholder support is considered essential in realizing relevant, effective and sustainable education policies.